Kebijakan Pengelolaan Limbah Industri UMKM Produksi Makanan dan Minuman terhadap Lingkungan di Kota Palangkaraya: The Policy of Industrial Waste Management for Food and Beverage Production MSMEs on the Environment in Palangkaraya City - Rahayu, Triwik Puji; Hariyanti, Anggelina (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
This study investigates waste management practices in small and medium enterprises (SMEs) in the food and beverage sector in Palangkaraya City. Interviews revealed low awareness and knowledge of waste regulations, as well as ineffective waste management practices. Major challenges include lack of knowledge, financial resources, and technology. The research highlights the need for intensive education, government support, and stakeholder collaboration to enhance sustainable waste management in SMEs.